An Investigation into the Practice of Stress Patterns in Arabic–Tamil Oral Translation Among Students of the Department of Arabic Language at South Eastern University of Sri Lanka: Reality and Aspirations - Shathifa, Mohammed Cassim Sithy; Majid, Mohamed Hasan Mohamed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Oral translation of Arabic to Tamil is among the greatest challenges because of the inherent disparity between the two languages’ phonological patterns, specifically in the area of stress. Stress is important in communicating meaning properly while oral translating; a mistake in the use of stress can introduce a change in meaning, thus influencing the perception of the listener. Students and translators face difficulties primarily due to their unfamiliarity with stress patterns and their lack of capability to properly transfer them from one language to another. The study aims to clarify the reality of students in applying stress in oral translation from Arabic to Tamil, and to identify their needs in this field. The researchers used qualitative and quantitative methods, using a descriptive-analytical approach. The primary data were gathered through interviews with four lecturers and questionnaires distributed to 39 students of specializations in the Arabic language and literature, linguistics and translation, academic year 2021/2022 at the Department of Arabic Language, South Eastern University of Sri Lanka. Furthermore, the researchers used secondary data such as books, research papers, articles, and academic theses, and Microsoft Excel to conduct data analysis. Outcomes indicated that there was a significant correlation between stress and oral translation. They realized that 73% of the students’ made mistakes in practice of stress pattern in oral translation such as: 32% made mistakes in applying stress in the Tamil language, 8% misplaced the stress, 8% put Tamil sentences in the wrong order according to stress, 4% made grammatical mistakes beforehand, and 21% changed the meaning of the sentences from positive to negative. These mistakes were caused by a lack of knowledge regarding stress in both languages, misusing stress, and a lack of proper training and practice.